National Seed Policy - Republic of Uganda, Ministry of Agriculture, Animal and Fisheries. - CGIAR Research Program on Water, Land and Ecosystems (2019)
The policy actions implemented have allowed the seed sub-sector to make a significant contribution to transformation from subsistence to commercial agriculture, improved food and nutrition security, increased household income and enhanced export earnings.